Evaluation of estrogenic chemicals in capsule and French press coffee using ultra-performance liquid chromatography with tandem mass spectrometry. (2020) - Sakaki, Junichi R.; Melough, Melissa M.; Provatas, Anthony A.; Perkins, Christopher; Chun, Ock K.
Highlights: Liquid chromatography with tandem mass spectrometry detected estrogenic chemicals in coffee. The potential risk to health is likely to be low relative to established guidelines. Future studies should evaluate the health risk from chronic coffee consumption. Abstract: The objective of this study was to examine exposure to estrogenic chemicals (ECs) via capsule coffee. Twenty-two brands of capsule coffee and 15 brands of French press coffee for comparison were brewed, and their contents of ECs were identified and quantified using ultra-performance liquid chromatography with tandem mass spectrometry. Exposure to ECs in coffee were compared to tolerable daily intake guidelines to assess potential hazard to health. Benzophenone was the most frequently detected EC in capsule coffee (mean concentration ± SD: 20.37 ± 47.07 ng/mL, n = 6), followed by bisphenol A (BPA, 0.31 ± 0.71, n = 4), dibutyl phthalate (1.41 ± 3.58, n = 3), 4-nonylphenol (0.67 ± 1.82, n = 3) and bisphenol F (BPF, 0.49 ± 1.54, n = 2). BPA and BPF were each detected in 3 French press coffee samples (0.29 ± 0.58 and 0.85 ± 1.75 ng/mL, respectively). Two French press coffee brands purchased as ground coffee rather than whole bean were positive for ECs (BPA in one and BPF in both). Hazard indexes were below 1.0 for each EC for both coffee types. These results indicate that there is EC contamination in capsule and French press coffee, but the quantities of ECs are low relative to established safety guidelines.